The Aventiinae, Boletobiinae, Eublemminae, Pangraptinae, Phytometrinae, and Scolecocampinae (Lepidoptera: Noctuoidea: Erebidae) of Great Smoky Mountains National Park, U.S.A. - Pogue, Michael G. (Zootaxa, 2012)
Twenty-five species of Erebidae are documented from Great Smoky Mountains National Park (GSMNP) from the follow-ing subfamilies: Aventiinae (1 species), Boletobiinae (7 species), Eublemminae (1 species), Pangraptinae (2 species), Phy-tometrinae (6 species), and Scolecocampinae (8 species). Each species is documented with an adult image, description/diagnosis, flight period, park distribution, abundance, elevational range, general distribution, and larval hosts. The mostcommon (155 specimens) and widespread (40 localities) species was Pangrapta decoralis Hübner. Scolecocampa liburna(Geyer) is the next most common (87 specimens) and widespread (30 localities). The most species rich locality was the combination of the 11 localities along the Foothills Parkway, Cocke Co., Tennessee.